To Assess Preparedness in Disaster Management among EMS Professionals in Pune, India - Parag Rishipathak1, Monesh Bhandari2, Anand Hinduja3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Natural disasters cause an estimated 60,000 deaths every year. Although low-frequency, highimpact events like earthquakes and tsunamis are not preventable, albeit loss of human lives can be preventedby developing an efficient disaster management system. In the last few decades robust emergency responsesystems, emergency preparedness, resilient infrastructure and accurate forecasting have significantlyreduced the death rate caused due to such calamities. Similar to natural disasters, MCIs drastically impactthe healthcare system and society at large.Emergency medical services (EMS) professionals play a pivotal role during disasters, mass casualty incidentsetc. and are an integral part of disaster management apparatus. The level of awareness and preparednessamongst EMPs with regards to disaster management is primordial. The areas requiring improvement includeskillset training strategic and operational planning and familiarity with the emergency preparedness indisaster management. Designing an effective training program for Indian EMS professionals, would requirea thorough understanding of the baseline level of preparedness among them.Objective: To assess preparedness in disaster management among Emergency Medical Professionals.Methodology: The study was conducted among Emergency Medical Professionals (EMPs) employed invarious hospitals in the city of Pune, India. The questionnaire tool utilized for the study was EmergencyPreparedness Information Questionnaire (EPIQ) a pretested and validated tool. The revised EPIQ toolcomprises of 42 items and is divided into eight sections.All 42 items were required to be mandatorily filled. The tool was administered through online mode. 119respondents reverted with completely filled questionnaire.Conclusion: Disasters although infrequent, cause significant morbidity and mortality. A high degree ofpreparedness is expected amongst EMP’s which can only be achieved with regular training and feedback.